Draft genome sequence of Streptomyces sp. strain M41isolated from soil in a conserved region of Sipadan Island,Sabah, Malaysia - Mardani Abdul Halim; Nur Ariffah Waly; Gerald Jetony; Ken Kartina Khamis; Colin Robinson; Nurul Akmar Hussin; Wong, Clemente Michael Vui Ling; Sazmal Effendi Arshad (American Society for Microbiology, 2025)
We present a draft genome of Streptomyces sp. isolated from soil in aconserved region of Sipadan Island, Sabah, Malaysia, and sequenced using the IlluminaNovaSeq 6000. The draft genome consists of 70 scaffolds with a total length of8,039,509 bp and a GC content of 70.9%. It contains 7,139 putative genes, includinggenes predicted to encode secondary metabolite biosynthesis.